Comprehensive clinical and virological characterization of three cases of fulminant liver failure owing to HSV1 primary infection. (7th March 2022) - Spahn, Stephan; Riessen, Reimer; Berg, Christoph P.; Malek, Nisar P.; Emrich, Marzena H.; Lohrengel, Kristina; Ganzenmueller, Tina; Iftner, Thomas; Kleymann, Gerald; Hamprecht, Klaus
Abstract: Herpes simplex virus 1 (HSV‐1) is a frequently unrecognized, yet deadly cause of acute liver failure (ALF). We, therefore, analysed three cases of fatal HSV‐1‐induced ALF. All patients shared clinical (extremely elevated transaminases, LDH and AST/LDH ratio < 1) and virological characteristics (ratio of viral load in plasma versus throat swabs: 60–700‐fold, lack of anti‐HSV‐1‐IgG antibodies or low IgG‐avidity during primary infection), which may help to identify patients at risk. Additionally, in vitro chemosusceptibility assays revealed high efficacy of the helicase‐primase inhibitors (HPI), pritelivir and drug‐candidate IM‐250 compared to acyclovir (ACV) using HSV‐1‐isolates from two patients; hence, ACV/HPI‐combinations might offer new therapeutic options for HSV‐induced ALF.